Religious Issue in Psychotherapy - Prawitasari, Johana E. (Faculty of Psychology, Universitas Surabaya, 2008)
Spirituality and religiosity are two different terms and different contexts. Religiosity is con- sidered as a term to be used related to religion, while spirituality will not be perceived as related to a- ny religion. Spirituality is a general term to refer to the attitude toward surrendering to the super pow- er beyond individual’s control. The tendency of psychotherapy to use religion in the process, I am afraid, will confuse the clients since they are asked to use their religion norms, yet their underlying problems are related to the norms. In the process of psychotherapy, therapist may offer different views of individuals’ existence. The two terms, religiosity and spirituality: the pro and contra in the psychotherapeutic process are discussed. Spiritualitas dan religiositas adalah dua istilah yang berbeda dan dipakai dalam konteks yang berbeda. Religiositas dipakai dalam kaitan dengan agama, sedangkan spiritualitas tidak diper- sepsikan terkait dengan agama mana pun. Spiritualitas adalah istilah umum yang merujuk pada sikap penyerahan diri pada kekuatan adikodrati di luar kendali individu. Kecenderungan psikoterapi mema- kai agama dalam prosesnya, menurut penulis, akan membingungkan klien mengingat mereka diminta menggunakan norma agamanya, pada hal penyebab masalahnya terkait norma tersebut. Dalam proses psikoterapi, terrapis dapat menawarkan pandangan yang berbeda mengenai eksistensi si individu. Di- diskusikan kedua isttilah, religiositas dan spiritualitas: yang pro maupun yang kontra dalam proses psikoterapi.